Infertility and Assisted Reproduction - Wang, Wei-Hua (IntechOpen, 2021)
Infertility affects approximately 15% of couples of reproductive age. High live birth rates rely on many advanced technologies in infertility treatment, including more accurate clinical diagnosis and patient management as well as state-of-the-art in vitro fertilization (IVF) technologies. This book discusses infertility and infertility treatments such as embryo implantation, non-invasive preimplantation genetic diagnosis (PGT), oocyte cryopreservation, cryopreservation of small numbers of sperm, and embryo culture technologies. It delivers new information and data valuable to clinicians, embryologists, and others in infertility treatment.